Pengembangan Skala Kesiapan akan Perubahan pada Mahasiswa Baru di Indonesia dan Uji Invariansi: Pendekatan MIMIC Model - Nur Pratama, Rizki; Rahman, Muchamad Salamun Abdul; Mukhlina, Nova; Imtiyaz, Muthmainnah; Mulika, Rifda Amira; Hartanto, Ricky Budhi; Khasanah, Ismi Uswatun (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study aims to modify the existing scale of readiness for change, because until today, the measurement of readiness for change has only been carried out for organizational settings. The researcher developed three dimensions of readiness for change in freshmant and the indicators were developed from a preliminary study. Participants in this study were freshman aged 17-19 at the D1, D2, D3, D4, and S1 education levels (n = 400). The measurments of instrument was carried out in several stages, namely normality test, model test with the Confiratory Factor Analysis (CFA) and Multiple Indicators Multiple Causes (MIMIC) approaches, and reliability test. The results showed that the Readiness for Change Scale in new students in Indonesia met the model fit criteria based on the CFI, TLI, RMSEA, and SRMR values. Reliability analysis also showed that this scale was stable or reliable. This study has novelty and contribution to the study of educational and developmental psychology, because there has not been much research measuring the readiness of freshman for various changes that occur during the transition to university.